2019
DOI: 10.3390/hydrology6040088
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Variability of Rainfall and Streamflow into Lake Nakuru, Kenya, Assessed Using SWAT and Hydrometeorological Indices

Abstract: Temporal variability analysis of rainfall and river discharges is useful in determining the likelihood of the occurrence of extreme events such as drought or flooding for the purposes of developing policies to mitigate their effects. This study investigated the temporal variability of rainfall and discharges into Lake Nakuru, Kenya using meteorological drought indicators and hydrological drought indicators from 1981 to 2018. The standardized precipitation index (SPI) and standardized precipitation evaporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…The SPI and SPEI values on a 6-month time scale oscillate between −2.5 and 2.0 ( Figure 5). Both dry and wet events were of lower intensity and longer duration, which is normal when the time scale is increased (Vicente-Serrano et al, 2010;Kimaru et al, 2019). In this scale, the SPI ( Figure 5A), is the only one that indicated that two extreme droughts took place in 2001 and 2005, in contrast to SPEI ( Figure 5B), which classifies the same droughts as severe.…”
Section: Spi and Spei Indicesmentioning
confidence: 93%
See 1 more Smart Citation
“…The SPI and SPEI values on a 6-month time scale oscillate between −2.5 and 2.0 ( Figure 5). Both dry and wet events were of lower intensity and longer duration, which is normal when the time scale is increased (Vicente-Serrano et al, 2010;Kimaru et al, 2019). In this scale, the SPI ( Figure 5A), is the only one that indicated that two extreme droughts took place in 2001 and 2005, in contrast to SPEI ( Figure 5B), which classifies the same droughts as severe.…”
Section: Spi and Spei Indicesmentioning
confidence: 93%
“…SPI and SPEI results for the city of Chachapoyas were calculated for the time scales of 3, 6, 12, and 24 months. On a three month scale, the series shows high frequency oscillation (Figure 4), due to the short time in which the variables are taken into account, thus changes are assimilated at great speed (Kimaru et al, 2019). The behavior of both indices is quite similar.…”
Section: Spi and Spei Indicesmentioning
confidence: 94%
“…e basin mean annual rainfall and evaporation within the basin is 1060 mm and 1292 mm, respectively. Further, the mean lake temperature ranges from 20.6°C to 23.5°C [15,21]. According to [25,26], poor waste disposal and anthropogenic influences in the watershed result in the sediment accumulation in the lake.…”
Section: Description Of the Studymentioning
confidence: 99%
“…Lake Nakuru has been fluctuating since the past 4 decades [13,15]. According to the studies [16][17][18][19][20][21] conducted from 1972 to 1985, the lake maximum water depth varied from 2.18 m to 4.18 m [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation